2017
DOI: 10.22159/ajpcr.2017.v10i5.17468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-Chronic Exposure to Chromium on Haematological and Biochemical Parameters of Male Albino Rat

Abstract: Objectives: Exposure to chromium, the transition element found in many compounds of earth's crust, leads to various health hazards including cancer, dermatitis, damage of liver and kidneys, and reproductive toxicity in both male and female. Toxic effect of chronic exposure to chromium at low environmentally relevant dose is recently recognized and less studied. In the present study, we evaluated the effect of subchronic exposure to low doses of chromium VI (K 2 Cr 2 O 7 ) on various hematological and biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
5
4
1
Order By: Relevance
“…This decrease reflects damage in hepatocytes and indicated the general and systemic toxic effect of heavy metals on rabbit does [36]. Similar results were reported by Saha et al, [31] in rats treated with potassium dichromate. An increase in cholesterol level in this study might be due to less utilization of these nutrients at the tissue level [37].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This decrease reflects damage in hepatocytes and indicated the general and systemic toxic effect of heavy metals on rabbit does [36]. Similar results were reported by Saha et al, [31] in rats treated with potassium dichromate. An increase in cholesterol level in this study might be due to less utilization of these nutrients at the tissue level [37].…”
Section: Discussionsupporting
confidence: 81%
“…This observation could signify that the dose of potassium dichromate administered did not have a pronounced effect on the anatomy of those organs. These results do not agree with Saha et al [31], who recorded a significant reduction in the weight of the reproductive organs along with an increase in the weight of the liver and kidney; and Petrovici et al [32], who noted an increase in ovary weight of rats exposed to potassium dichromate at a dose of 10 mg/kg bw with respect to the control.…”
Section: Discussioncontrasting
confidence: 67%
“…While Saha et al (2017) found increase in plasma glucose and cholesterol levels of the exposed rats to Cr (6) and Yousif and Ahmed (2009) attributed that to defect in utilization of these nutrients at tissue level due to toxicity of Cr (6). Chromium (6) increased cholesterol level in cells by upregulating cholesterol-synthesizing enzymes (Guo et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Semen analysis showed that sub chronic exposure to Cd and Cr resulted in a significant decrease in total sperm count and viability with a significant increase in the percent of sperms with abnormal morphology. Cadmium induced damage to the testicular germinal epithelium, the Leydig cells and the Sertoli cells resulting Mans Vet Med J 20:3 (2019) [14][15][16][17][18] in testicular and cellular damage which adversely affected sperm characters [7,26]. Exposure to Cd disrupted the tight junctions between Sertoli cells and altered germ cell adhesion with consequent exfoliation of immature cells into the lumen of seminiferous tubules, leading to a decrease in viable sperm count [37].…”
Section: Discussionmentioning
confidence: 99%